2021
DOI: 10.1080/14737159.2021.1933449
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of seven commercial molecular in vitro SARS-CoV-2 detection tests: a rapid meta-analysis

Abstract: Objective : To compare the accuracy parameters of seven commercial molecular in vitro diagnostic tests for detecting SARS-CoV-2. Methods : Studies evaluating the accuracy of seven different commercial molecular diagnostic tests for detecting SARS-CoV-2 (Cepheid Xpert Xpress SARS-CoV-2 test, Simplexa COVID-19 Direct, Abbott ID NOW COVID-19, Cobas SARS-CoV-2, Allplex 2019-nCoV Assay, Panther Fusion SARS-CoV-2, and BioFire COVID-19 Test) were included. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…We found that Xpert ® Xpress SARS-CoV-2 test had the highest sensitivity among all tests, compared to the reference kit. This finding was not surprising in light of data from previous publications that have presented even higher sensitivities of this assay (97–100%), compared to the current study [ 7 9 ]. Additionally, a recent report that compared the performances of seven different primer-probe sets concluded that primers that target the N2 or the E genes, as in the Xpert ® Xpress SARS-CoV-2 test, have higher sensitivity, compared to primers with other gene targets [ 10 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that Xpert ® Xpress SARS-CoV-2 test had the highest sensitivity among all tests, compared to the reference kit. This finding was not surprising in light of data from previous publications that have presented even higher sensitivities of this assay (97–100%), compared to the current study [ 7 9 ]. Additionally, a recent report that compared the performances of seven different primer-probe sets concluded that primers that target the N2 or the E genes, as in the Xpert ® Xpress SARS-CoV-2 test, have higher sensitivity, compared to primers with other gene targets [ 10 ].…”
Section: Discussionsupporting
confidence: 78%
“…For example, in the current study, all assays were compared to the Allplex™ 2019-nCoV Assay. Different studies have used other assays as their reference kit [ 7 9 , 11 , 12 ]. Therefore, the performance of a specific kit may change when compared to a different assay.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many commercial SARS-CoV-2 nucleic acid POCT products for COVID-19 have been granted emergency use authorization (EUA) by the Food and Drug Administration (FDA) to identify SARS-CoV-2-positive patients, including the Xpert Xpress SARS-CoV-2 test (Cepheid), ID NOW COVID-19 (Abbott Diagnostics Scarborough, Inc.), BioFire COVID-19 Test (BioFire Defense, LLC), Simplex COVID-19 Direct (DiaSorin Molecular LLC), Cobas SARS-CoV-2 (Roche Molecular Systems, Inc.), Panther Fusion SARS-CoV-2 (Hologic, Inc.), and Allplex SARS-CoV-2 Assay (Seegene Inc.) [ 7 ]. Studies on the performance of these seven FDA-approved and commercially available SARS-CoV-2 nucleic acid POCT products showed that the overall performance of commercial SARS-CoV-2 nucleic acid POCT products was high, with a summary sensitivity of 95.9% (95% CI 93.9–97.2%, I2 = 60.22%) and specificity of 97.2% (95% CI 95.5–98.3%, I2 = 56.66%) [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. However, the ID NOW COVID-19 (Abbott) and the Simplex COVID-19 Direct exhibited lower sensitivity than other platforms, consistent with previously reported studies [ [9] , [10] , [11] , [12] , [13] , [14] ].…”
Section: Current Mainstream Commercial Sars-cov-2 Nucleic Acid Poct Productsmentioning
confidence: 99%
“…[ 2 , 3 ] Huge scientific advances have been made in COVID-19 diagnosis, and several high-performance technologies have been developed in recent years. 2 , 3 , 4 Consequently, it is essential to select cost-effective diagnostic methods for monitoring in a different type of action settings, especially in ambulatory care backgrounds, where case management, isolation, contact tracing and quarantine are relevant to prevent viral transmission in the community. [3] …”
Section: XXXmentioning
confidence: 99%